Formation of changing coalitions in EU agricultural policy - conceptualization assumptions for political science research - Miecznikowska, Justyna (Wydział Nauk Politycznych i Dziennikarstwa Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2019)
This article is a conceptualization study aiming to provide the groundwork for research into the formation of changing coalitions among European Union Member States. Firstly, it as- sesses the current state of research, follows with a selection of research problems and provides validation for the research considerations raised. It poses research hypotheses and questions that verify the hypotheses. The latter part of the article attempts to identify the paradigms, tech- niques and tools able to diagnose the research problems posed.

Artykuł jest opracowaniem konceptualizacyjnym stanowiącym przygotowanie do badań nad kształtowaniem się zmiennych koalicji między państwami członkowskimi w polityce rolnej Unii Europejskiej. W pierwszej kolejności dokonana została ocena stanu badań, następnie prze- selekcjonowano problemy uzasadniając zasadność prowadzonych rozważań. Zaproponowano hipotezy badawcze wraz z pytaniami prowadzącymi do weryfikacji hipotez. W dalszej części artykułu podjęto próbę wskazania paradygmatów oraz technik i narzędzi pomocnych w zdia- gnozowaniu zaproponowanych problemów badawczych.
Kształtowanie się zmiennych koalicji w polityce rolnej Unii Europejskiej – założenia konceptualizacyjne badań politologicznych
Keywords: European Union; Common Agricultural Policy; coalitions; EU member states; Multiannual Financial Framework; Unia Europejska; Wspólna Polityka Rolna; koalicje; państwa członkowskie UE; Wieloletnie Ramy Finansowe